Contribution of diversity of social participation on the mental health of humanitarian migrants during resettlement - Weiqing Jiang; Yuwei Yang; Yitong He; Qianyu Liu; Xueqing Deng; Yilin Hua; Alimila Hayixibayi; Yanyan Ni; Lan Guo (Cambridge University Press, 2024)
Abstract Aims By the end of 2022, an estimated 108.4 million individuals worldwide experienced forced displacement. Identifying modifiable factors associated with the mental illness of refugees is crucial for promoting successful integration and developing effective health policies. This study aims to examine the associations between the changes in the diversity of social participation and psychological distress among refugees throughout the resettlement process, specifically focusing on gender differences. Methods Utilizing data from three waves of a longitudinal, nationally representative cohort study conducted in Australia, this study involved 2399 refugees interviewed during Wave 1, 1894 individuals interviewed during Wave 3 and 1881 respondents during Wave 5. At each wave, we assessed psychological distress and 10 types of social participation across 3 distinct dimensions, including social activities, employment and education. The primary analysis employed mixed linear models and time-varying Cox models. Gender-stratified analyses and sensitivity analyses were performed. Results Refugees engaging in one type or two or more types of social participation, compared with those not engaging in any, consistently had lower psychological distress scores (β = −0.62 [95% confidence interval (CI), −1.07 to −0.17] for one type of social participation; β = −0.57 [95% CI, −1.04 to −0.10] for two or more types of social participation) and a reduced risk of experiencing psychological distress (hazard ratio [HR] = 0.81 [95% CI, 0.65-0.99] for one type of social participation; HR = 0.77 [95% CI, 0.61-0.97] for two or more types of social participation) during the resettlement period. When stratifying the results by gender, these associations in the adjusted models only remained significant in male refugees. Moreover, three specific types of social participation, namely sporting activities, leisure activities and current employment status, were most prominently associated with a reduced risk of psychological distress. Conclusions The findings of this cohort study suggest that social participation was consistently associated with reduced risks of psychological distress among male refugees during resettlement. These findings highlight the significance of promoting meaningful social participation and interaction may be an effective strategy to improve the mental health of refugees and facilitate their successful integration into society, especially among male refugees.